Treatment of perineal wounds using complementary alternative therapies: Evidence based case review - Lailatul Rahmah; Fitri Yuliana; Adriana Palimbo; Rabia Wahdah; Irma Putri Rahayu (Ananda - Health & Education Foundation, 2024)
Background: Perineal wounds can cause pain, inflammation, and mechanical trauma and even affect daily mobility. Furthermore, over a long period, prolonged pain can also cause women to become irritable, tired, and even depressed. Midwives are responsible for providing episiotomy pain management services and offering evidence-based good practices for such problems or complaints. Objective: This evidence-based case review aims to determine the results of alternative treatments in relieving and healing perineal wound pain, both spontaneous tears during childbirth and suture wounds. Method: This review is based on a good practice stage report carried out by a group of midwife professional program students who handled midwifery care in the Fatimah Azzahra postpartum ward, Islamic Hospitals, Banjarmasin, in June 2023 with cases including spontaneous lacerations, episiotomies, and second-degree suturing. Then, three articles were assessed and analyzed to provide comparison and evidence relevant to our case report. Criteria indicators use the PICO format. Findings: The problem was seen in episiotomy wound pain, with some differences in intervention, including lavender oil, ice blocks, rosemary cream, and lavender oil vapor. Furthermore, the comparison between the studies was the group of material used, method, and design of interventions. The outcomes were reduced local temperature of the skin and subcutaneous tissue and a lower rate of the wound in the intervention. Conclusion: Complementary therapy of midwifery care in hospitals has been implemented quite well as long as it does not conflict with procedures, raw materials are easy to obtain, and it is also under continuous supervision by other practitioners.